Metal–Organic Framework Materials for Electrochemical Supercapacitors - Cao, Ziwei; Momen, Roya; Tao, Shusheng; Xiong, Dengyi; Song, Zirui; Xiao, Xuhuan; Deng, Wentao; Hou, Hongshuai; Yasar, Sedat; Altin, Sedar; Bulut, Faith; Zou, Guoqiang; et al. (Nano-Micro Letters, 2022)
Exploring new materials with high stability and capacity is full of challenges in sustainable energy conversion and storage systems. Metal–organic frameworks (MOFs), as a new type of porous material, show the advantages of large specific surface area, high porosity, low density, and adjustable pore size, exhibiting a broad application prospect in the field of electrocatalytic reactions, batteries, particularly in the field of supercapacitors. This comprehensive review outlines the recent progress in synthetic methods and electrochemical performances of MOF materials, as well as their applications in supercapacitors. Additionally, the superiorities of MOFs-related materials are highlighted, while major challenges or opportunities for future research on them for electrochemical supercapacitors have been discussed and displayed, along with extensive experimental experiences. Highlights: 1 The classification of metal–organic frameworks (MOFs) is summarized: MOFs can be divided into one, two and three dimensions based on the skeletal structure, MOFs can be divided into isoreticular metal organic frameworks, zeolitic imidazolate frameworks, and so on according to the ligand. 2 The preparation methods of MOFs are reviewed, which can be divided into traditional one pot method and the emerging preparation methods. 3 The application of MOF materials, MOF composite materials, and MOFs-derived materials in supercapacitor is emphasized.